Development and Design of Intelligent Gymnasium System Based on K-Means Clustering Algorithm Under the Internet of Things - Yin, Han; Xu, Jian; Luo, Zebin; Xu, Yiwen; He, Sisi; Xiong, Tao (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
With the rapid development of the Internet of things technology in today’s society, the optimization design and development of intelligent stadium system has become a major trend. Based on the analysis of the requirements of the Internet of things technology for system design, the K-means clustering algorithm of customer classification is used to design an athlete-centered system to improve the service quality of athletes; the system architecture model based on the network is used to realize information interaction and resource sharing among users with different roles. Taking athletes and service management as the core content of the system design and development, the intelligent stadium system is optimized from the system outline structure, system function, Internet of things architecture, and other aspects. The results show that the development and design of the intelligent stadium system under the Internet of things technology is helpful to realize the intelligent management of the stadium, and also can improve the management efficiency of the intelligent stadium, increase 28.0%, and play a positive application benefit. The research results show that under the Internet of things technology, the development and design of an intelligent stadium system can play a positive role and can be applied in practice. The positioning deviation of the original system is corrected.